2009
DOI: 10.1021/nn900848x
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Assembly of ZnO Nanostructures on SnO2 Backbone Nanowires: Low-Temperature Hydrothermal Preparation and Optical Properties

Abstract: Hierarchical nanostructures with SnO(2) backbones and ZnO branches are successfully prepared in a large scale by combining the vapor transport and deposition process (for SnO(2) nanowires) and a hydrothermal growth (for ZnO). The ZnO nanorods grow epitaxially on the SnO(2) nanowire side faces mainly with a four-fold symmetry. The number density and morphology of the secondary ZnO can be tailored by changing the precursor concentration, reaction time, and by adding surfactants. Photoluminescence (PL) properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
180
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(182 citation statements)
references
References 50 publications
2
180
0
Order By: Relevance
“…Raman scattering can give evidence about the crystal structure on the scale of a few lattice constants. Therefore, Raman spectroscopic technique is one of the useful methods to achievement deep into the nanostructure structural [33]. The sharp peak at 438 cm -1 corresponding to E 2 (low) and E 2 (high) are characteristic of hexagonal wurtzite structure of high crystalline quality (Fig.5).…”
Section: Resultsmentioning
confidence: 99%
“…Raman scattering can give evidence about the crystal structure on the scale of a few lattice constants. Therefore, Raman spectroscopic technique is one of the useful methods to achievement deep into the nanostructure structural [33]. The sharp peak at 438 cm -1 corresponding to E 2 (low) and E 2 (high) are characteristic of hexagonal wurtzite structure of high crystalline quality (Fig.5).…”
Section: Resultsmentioning
confidence: 99%
“…Some reasons were proposed to explain such phenomenon: First, the ZnO nanorods may compensate the defects on the surface of the SnO 2 nanowire. 32 Second, SnO 2 is surrounded by ZnO nanorod, the excitation light was almost absorbed by the ZnO nanorods. Third, the PL from the SnO 2 nanowires is much weaker than that from ZnO nanorods, so the PL peak from the SnO 2 can not emerge out.…”
Section: Resultsmentioning
confidence: 99%
“…[26][27][28][29][30][31] Because of similar bandgap and optoeletronics functions of ZnO and SnO 2 , hybrid ZnO/SnO 2 threedimensional hierarchical nanostructures were fabricated and investigated. [32][33][34] Cheng et al reported hierarchical nanostructures composed by SnO 2 backbones and ZnO branches, random lasing was observed from the ZnO branches where the multiscattering was easy to be generated. 32 Liu et al reported flower-like hierarchical structures with ZnO backbones and SnO 2 branches using chemical method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another advantage of ALD is its relatively low deposition temperature. Compared with conventional CVD techniques that are often conducted in the temperature range of 600–1050 °C,7 ALD can be run in temperatures below 300 °C. In addition, some materials can be effectively deposited below 100 °C or even at room temperature 8.…”
Section: Introductionmentioning
confidence: 99%